Reductive Functionalization of C–C π-Bonds via Alkene Radical Anions - Franov, Liam J.; Wilsdon, Tayla L.; Polyzos, Anastasios (Synlett, 2025)
Alkene radical anions are powerful yet underutilized intermediates for the construction of C(sp3)–C(sp3) bonds in organic synthesis. This Synpacts article provides an overview of established methods for their generation and functionalization via photoredox catalysis and electrosynthesis. In particular, we highlight our recent development of an electroreductive alkene–aldehyde coupling enabled by rapid alternating polarity. This waveform allows the chemoselective generation of alkene radical anions from vinylarenes and heterocycles and directs their reactivity toward C–C bond formation with alkyl aldehydes to furnish structurally diverse secondary alcohols.
Keywords: Radical anions; Alkenes; Aldehydes; Electrosynthesis; Rapid alternating polarity; Photochemistry